A Search for self-therapy from the sense of loss due to high modernism in Haruki Murakami’s South of the Border, West of the Sun (International Journal of Food and Nutritional Sciences, 2022)
This research on Murakami’s novel South of the Border, West of the Sun attempts to disclose the sense of loss and a search for Self-therapy from the modernist perspective. Modernity is related to the modern era and the aesthetic qualities of modernism; however, modernity refers specifically to the social conditions and relations that arise out of the modern period, usually as a result of capitalism and industrialization. Modernity and high modernity are concerned with human progress and the potential of human intervention to bring down positive change in the structure of society; however, high modernity’s visions of societal change rely on the expertise of intellectuals and scientific innovation, making high modernity a more elitist project than its predecessor. This paper argues that separation, loss, and alienation of characters that one meets in his/her life do not let him live a happy life. In fact, coping with loss, search for self-therapy and growing to search for commitment make people to live a satisfied and illumined life. It is the product of modernism that the protagonists of this novel Hajime and Shimamoto are dissatisfied with each other and they slip away from reality. Also, Murakami portrays Hajime lamenting on the loss of his youthful days which leads as a psychologically weak mentality of his own leads his life into a tragic track. The problems that are identified in this novel are social by nature, no science except modernism can address such issues, and therefore the modernist perspective explores social problems faced by the protagonist and paving way for the way of resolution.